THE EFFECT OF COMPANY SIZE AND POLITICAL CONNECTIONS ON TAX AVOIDANCE - Novi Hadzida; Ifan Wicaksana Siregar (ZILLZELL MEDIA PRIMA, 2024)
The objective of this study is to examine The Effect of Company Size and Political Connections on Tax Avoidance Practices amongst Agricultural companies listed on the Indonesia Stock Exchange between the years 2018 to 2022. The size of a company is gauged by the natural logarithm of its total assets, while political connections are quantified through the use of a dummy variable, with a value of one denoting connected companies and a value of zero denoting unconnected ones. Finally, the extent of tax avoidance is measured through Book-to-Tax Differences (BTD). This study’s population was comprised of agricultural companies that were listed on IDX between the years 2018 to 2022. The sample consisted of 8 companies and a total of 40 data points were collected through a purposive sampling method. The type of research is quantitative, using multiple linear regression and IBM SPSS software version 25 for data analysis. The research findings suggest that Company Size significantly negatively effect on Tax Avoidance, whereas Political Connections was found to have no effect on Tax Avoidance. However, when considered simultaneously, Company Size and Political Connections have a significantly effect on Tax Avoidance in agricultural companies listed on the IDX between the years of 2018 to 2022.